Nomenclature and taxonomy of the species described in 1883 and in 1890 by John Gilbert Baker (1834–1920) in the genus Bryophyllum, basionym of Kalanchoe subg. Bryophyllum (Crassulaceae subfam. Cotyledonoideae) - Smith, Gideon F. (Phytotaxa, 2025)
Kew botanist John Gilbert Baker (1834–1920) described two species in Bryophyllum, which, when upheld as an accepted genus, is included in Crassulaceae subfam. Cotyledonoideae. The two species are B. crenatum and B. rubellum. Bryophyllum was in the past variously recognised at the rank of genus in the subfamily, but is today accepted as a subgenus in Kalanchoe, as K. subg. Bryophyllum. The nomenclature and taxonomy of the two species names published in Bryophyllum by Baker are reviewed and discussed in a historical context. The typification of the names B. crenatum, a heterotypic synonym of K. laxiflora, and B. rubellum, the basionym of K. rubella, is clarified.